MAKNA TILAWAH, TAZKIYAH, TA’LIM AL-KITAB WA AL-HIKMAH DAN IMPLEMENTASINYA DALAM PEMBELAJARAN: TELAAH SURAT AL-JUMUAH AYAT 2 - Asmuki Asmuki; Imam Taufiq (Fakultas Tarbiyah, Universitas Ibrahimy, 2021)
The problems of life such as moral decadence always occur in society, specifically students. Because of that, it is needed right solution to solve that matter. One of the ways to solve that through properly understanding Alquran the content of QS. Al-Jumuah ayah 2 for educators. There are three kinds implementation of Surah al-Jum'ah in learning activities. The first is tilawah ayah, that the teacher gives aqidah studies for student suitable with student's education level. The second is tazkiyah, that the teacher cleans misguided aqidah and bad behavior. The third is ta'limu al-Kitab wa al-Hikmah, this stage has the meaning that teacher teach the essential material for student, and continuing to teach other material (alhikmah). another meaning is to prioritize religious sciences, after that move to other sciences (al-hikmah).